Biomasa de raíces finas en cuatro estadíos de sucesión del Bosque Seco Tropical y dos estaciones climáticas, Santa Rosa, Costa Rica - Mullins-Riley, Shari (Instituto Tecnológico de Costa Rica, 2011)
In Costa Rica, tropical dry forests had suffered the effects of land change for a long time; Hence, the study of fine roots ( ≤ 2mm diameter) among successional forest stages would allow us to evaluate the degree of these disturbances. I studied fine root biomass up to 40 cm soil depth along a successional gradient in two climatic seasons; rainy (November 2010) and dry (March 2011.The dry season resulted with more fine root biomass; according to the literature this is a strategy to capture water and nutrients from deeper soil layers. The rainy season resulted with no significant differences among total fine root biomass (p>0,05); late forest obtain 361,943 g/m2 of fine root biomass, pastures had 341,760 g/m2 ; early and intermediate forests obtained 313,140 ; 297,651 g/m2 respectively. In the dry season, significant differences where found (p< 0,05) among the following three groups early forest (520,713 g/m2), pastures (224,693 g/m2) and intermediate (362,083 g/m2 ) plus late (419,823 g/m2 ). Finally I compared the total fine root biomass between dry and rainy seasons and only significant differences where found for early stage; rainy (313,140 g/m2) versus dry (520,713 g/m2). I conclude that there is a clear trend of increasing fine root biomass along the successional stages, however no stadistical significant differences were found probably because the sample size and sampling system should be improved.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Forestal, 2011.
Keywords: Ecosistemas; Nutrientes; Microorganismos; Agua; Infiltración; Aireación del suelo